A habitação e o saneamento no cotidiano dos moradores de um conjunto habitacional em Belo Horizonte: um estudo das representações dos sujeitos sobre sua condição sanitária - Dayse Magnani de Souza (2007)
Mans improper behavior towards the environment has caused several problems, resulting in consequences not only to the environment, but also to peoples quality of life. The subjects dedicated to the study of the behavior/environment relation rely on concepts that inter-relateknowledge and conduct. One of these concepts suggests that each individual knows the environment where they live in a unique way and that this awareness dictates their behavior towards the environment. The theory of social representations, formulated by Serge Moscovici in 1961, deals with this knowledge as legitimate, distinguished from scientificknowledge, for its importance in social life and for explaining the cognitive processes and interactions with the world. This kind of knowledge, named social representation, is socially elaborated and shared and it has a practical function, contributing to the construction of a reality common to a social group. The research aims at investigating the way residents from a housing complex in Belo Horizonte understand the elements of sanitation and housing, here dealt as essential elements to peoples quality of life, as housing is the place of life and interaction of individuals with their sanitary structure. The qualitative methodology was used for the investigation and interviews were used as method of collecting data. The Discurso do Sujeito Coletivo was used as method of analysis. Twelve citizens from Conjunto Novo Aarão Reis were interviewed in their homes, since this is considered the place of greater possibility of subject/object interaction. The data found showed that the residents have a sanitary past marked by the absence of basic sanitation services and a great effort to obtain the current sanitary conditions. They consider their neighborhood and homes as good places to live in,and that enhances their feeling of privilege in living there as in contrast to other neighborhoods. They recognize in the sanitary infrastructure (in their homes and neighborhood) as elements capable of improving health, environment and quality of life. The impression of the technicians who studied the place resembles the one presented by the residents in relation to the identification of the problems, and this impression differs when considering the qualities. In general, the representations identified correspond to the practices mentioned. The results obtained provide data to guide not only programs of sanitary and environmental education, or of promotion of health and hygiene, but also programs for community development.